2015
DOI: 10.1371/journal.pone.0117737
|View full text |Cite
|
Sign up to set email alerts
|

Genome Wide Association Study for Drought, Aflatoxin Resistance, and Important Agronomic Traits of Maize Hybrids in the Sub-Tropics

Abstract: The primary maize (Zea mays L.) production areas are in temperate regions throughout the world and this is where most maize breeding is focused. Important but lower yielding maize growing regions such as the sub-tropics experience unique challenges, the greatest of which are drought stress and aflatoxin contamination. Here we used a diversity panel consisting of 346 maize inbred lines originating in temperate, sub-tropical and tropical areas testcrossed to stiff-stalk line Tx714 to investigate these traits. Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
2

Relationship

6
4

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 117 publications
(170 reference statements)
3
95
0
1
Order By: Relevance
“…Testing of multiple hybrids across diverse environments has been also used in genetic study. For example, testcrosses between Tx714 and 346 diverse inbreds evaluated under well watered and non-irrigated trials showed high genetic variance, and for 10 quantitative trait variants for agronomic traits as revealed by 60,000 SNPs, three of them explained 5–10% of phenotypic variation in grain yield under both water conditions44. In our research, hybrids from the MHP showed a high level of genetic and phenotypic variation across different environments (data not shown).…”
Section: Multiple-hybrid Populations (Mhp) For Gwasmentioning
confidence: 50%
“…Testing of multiple hybrids across diverse environments has been also used in genetic study. For example, testcrosses between Tx714 and 346 diverse inbreds evaluated under well watered and non-irrigated trials showed high genetic variance, and for 10 quantitative trait variants for agronomic traits as revealed by 60,000 SNPs, three of them explained 5–10% of phenotypic variation in grain yield under both water conditions44. In our research, hybrids from the MHP showed a high level of genetic and phenotypic variation across different environments (data not shown).…”
Section: Multiple-hybrid Populations (Mhp) For Gwasmentioning
confidence: 50%
“…The relatively low levels of residual variation for all traits were encouraging, given that single replications among experimental entries (in a single environment) can lead to unaccounted sources of variation. Accounting for field variation with blocking or other methods is always useful to test but often carries increased importance for yield trials in Texas where furrow irrigation is used, as it was here (Barrero et al, 2015). Across all five environments (Table 3), field variation (block) was significant, but the proportion of the total variation (2.4-6.6%) coming from this effect was low.…”
Section: Genetic Variation Observed For All Agronomic Traits Analyzedmentioning
confidence: 99%
“…GWAS generally have better mapping resolution than biparental mapping and have become more widely available to plant researchers (Gao, Kathryn Turner, Chao, Kolmer, & Anderson, ). In maize, GWAS have been used successfully to study agronomic traits (Farfan et al, ; Tian et al, ), quality traits (Owens et al, ; Suwarno, Pixley, Palacios‐Rojas, Kaeppler, & Babu, ), pest resistance (Samayoa, Malvar, Olukolu, Holland, & Butrón, ) and disease resistance (Coan et al, ; Gowda et al, ; Zila et al, ).…”
Section: Introductionmentioning
confidence: 99%